2020
DOI: 10.1021/acs.oprd.0c00159
|View full text |Cite
|
Sign up to set email alerts
|

Potential Explosion Hazards Associated with the Autocatalytic Thermal Decomposition of Dimethyl Sulfoxide and Its Mixtures

Abstract: Dimethyl sulfoxide (DMSO) is widely used as a solvent for chemical reactions, as a cosolvent for crop protection formulations, and in medicines for topical administration of drugs. The potential explosion hazards associated with thermal decomposition of DMSO have been well-documented, with early reports dating back to the late 1950s. However, these explosion hazards are still underappreciated and inadequately communicated, as indicated by the fact that numerous severe accidents have occurred on both laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 132 publications
3
78
0
Order By: Relevance
“…In addition, decomposition of DMSO at elevated temperature raises potential safety issues. [14] Moreover, in their report, hydrogenation of technical-grade polymers was not demonstrated. Here, we disclose our results on rutheniumcatalyzed hydrogenation of polyamides and polyurethanes through cleavage of the CÀ N bond of amide and carbamate groups.…”
mentioning
confidence: 93%
“…In addition, decomposition of DMSO at elevated temperature raises potential safety issues. [14] Moreover, in their report, hydrogenation of technical-grade polymers was not demonstrated. Here, we disclose our results on rutheniumcatalyzed hydrogenation of polyamides and polyurethanes through cleavage of the CÀ N bond of amide and carbamate groups.…”
mentioning
confidence: 93%
“…DMSO has been reported as an effective oxidant. [21] However, only 15% yield of the bipyrazine was afforded when PhNO 2 was replaced with DMSO in this case (entry 6). Other oxidants such as H 2 O 2 , K 2 S 2 O 8 and Selectfluor failed to give the expected dimeric pyrazines (entry 7).…”
Section: Resultsmentioning
confidence: 95%
“…13 1 Hz, 2H), 3.17 (t, J = 5.2 Hz, 4H), 3.03 (t, J = 5.2 Hz, 4H), 2.05-1.99 (m, 8H). 13 [21] Petroleum ether/ethyl acetate [24] Petroleum ether/ethyl acetate = 1:1; cis-7, yellow solid (100 mg, 32%); mp 131-132 °C; 1 H NMR (400 MHz, CDCl 3 ) δ 7.44 (d, J = 7.4 Hz, 4H), 7.41-7.28 (m, 6H), 6.15 (s, 2H), 4.50 (dt, J = 13.5, 3.4 Hz, 1H), 2.76 (s, 1H), 1.87-1.76 (m, 1H), 1.68-1.57 (m, 1H), 1.54-1.39 (m, 2H), 1.13-1.04 (m, 4H). 13 The NMR data were identical in all respects to those previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…During the experiment, it was found that the treated samples can also completely dissolve in the LiCl/DMSO solvent system by direct stirring at 60 °C for only 6 h. It should be noted that the dissolution temperature should not exceed 90 °C to prevent the disproportionation reaction of dimethyl sulfoxide. 39,40 The reason why chemical treatment reduces the dissolving capacity of the lignocellulosic biomass samples in the LiCl/DMSO solvent system and the influence of temperature on the solubility of biomass samples still need further systematic studies. However, the extraordinary solubility of lignocellulosic biomass in the LiCl/DMSO solvent system under mild conditions without chemical pretreatment provides a promising prospect for the development of subsequent green quantitative methods of lignin.…”
Section: Dissolution Characteristics Of Lignocellulosic Biomass In a ...mentioning
confidence: 99%